Prenatal diagnosis of 24 cases of microduplication 22q11.2: an investigation of phenotype‐genotype correlations. (16th September 2014) - Dupont, Céline; Grati, Francesca Romana; Choy, Kwong Wai; Jaillard, Sylvie; Toutain, Jérôme; Maurin, Marie‐Laure; Martínez‐Conejero, Jose Antonio; Beneteau, Claire; Coussement, Aurélie; Molina‐Gomes, Denise; Horelli‐Kuitunen, Nina; Aboura, Azzedine; et al.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Fluorescence in situ hybridization analysis of the 22q11.2 region in a large cohort of children referred for DiGeorge syndrome/velocardiofacial syndrome led to the identification of a new chromosomal syndrome:microduplication 22q11.2. This syndrome has a highly variable clinical phenotype. What does this study add? This study is the first prenatal series about the 22q11.2 microduplication syndrome (24 cases). We searched for possible correlations between fetal phenotypes, indications for invasive prenatal diagnosis, inheritance, pregnancy outcomes, and presence of others copy number variations.